Вплив умов праці робітників ливарних виробництв на розвиток професійних захворювань - Райко, Валентина Федорівна; Османова, Ольга Вікторівна (Яроче́нко Я. В., 2022)
A complex of production factors affecting the safety and health of workers in foundry production has been determined. The state of occupational morbidity in foundry production was determined. It was determined that the most common disease among foundries is dust exposure (dust bronchitis).
Keywords: ливарне виробництво; безпека працівників; несприятливі параметри; професійна захворюваність; професійні захворювання; силікоз; пиловий бронхіт